Features of the system of epidemiological surveillance of infectious diseases in the Socialist Republic of Vietnam - V. T. Hoang; A. A. Kuzin; A. E. Zobov; A. A. Zobovа (Журнал инфектологии, 2023)
The results of the analysis of the system of epidemiological surveillance of infectious diseases in the Socialist Republic of Vietnam and the assessment of the possibilities of its improvement are presented. The levels of organization of epidemiological surveillance in Vietnam, their compliance with the administrative division of the country (state, provincial, district and commune levels) are shown. It is noted that epidemiological surveillance has a passive nature and is based on the online reporting system of the Department of Preventive Medicine, which has been the official notification channel for 42 infectious diseases since 2016. For the purposes of epidemiological surveillance, all registered infectious diseases are divided into 3 groups according to the potential for epidemic spread (A, B and C), on which strategies for carrying out sanitary and anti-epidemic (preventive) measures depend. It has been established that modern computer technologies, including geoinformation systems, in Vietnam have found their application in certain areas of epidemiological surveillance of current infectious diseases, but further improvement of the methods of their use for these purposes is required.